Assessment of Inspiratory Effort in Spontaneously Breathing COVID-19 ARDS Patients Undergoing Helmet CPAP: A Comparison between Esophageal, Transdiaphragmatic and Central Venous Pressure Swing - Sergio Lassola; Sara Miori; Andrea Sanna; Ilaria Menegoni; Silvia De Rosa; Giacomo Bellani; Michele Umbrello (Diagnostics, 2023)
Introduction: The clinical features of COVID-19 are highly variable. It has been speculated that the progression across COVID-19 may be triggered by excessive inspiratory drive activation. The aim of the present study was to assess whether the tidal swing in central venous pressure (ΔCVP) is a reliable estimate of inspiratory effort. Methods: Thirty critically ill patients with COVID-19 ARDS underwent a PEEP trial (0–5–10 cmH2O) during helmet CPAP. Esophageal (ΔPes) and transdiaphragmatic (ΔPdi) pressure swings were measured as indices of inspiratory effort. ΔCVP was assessed via a standard venous catheter. A low and a high inspiratory effort were defined as ΔPes ≤ 10 and  >15 cmH2O, respectively. Results: During the PEEP trial, no significant changes in ΔPes (11 [6–16] vs. 11 [7–15] vs. 12 [8–16] cmH2O, p = 0.652) and in ΔCVP (12 [7–17] vs. 11.5 [7–16] vs. 11.5 [8–15] cmH2O, p = 0.918) were detected. ΔCVP was significantly associated with ΔPes (marginal R2 0.87, p < 0.001). ΔCVP recognized both low (AUC-ROC curve 0.89 [0.84–0.96]) and high inspiratory efforts (AUC-ROC curve 0.98 [0.96–1]). Conclusions: ΔCVP is an easily available a reliable surrogate of ΔPes and can detect a low or a high inspiratory effort. This study provides a useful bedside tool to monitor the inspiratory effort of spontaneously breathing COVID-19 patients.